Transcriptome Profiling of Lung Innate Immune Responses Potentially Associated With the Pathogenesis of Acinetobacter baumannii Acute Lethal Pneumonia - Zeng, Xi; Gu, Hao; Peng, Liusheng; Yang, Yao; Wang, Ning; Shi, Yun; Zou, Quanming (Frontiers in Immunology, 2020)
Acinetobacter baumannii is one of the dominating causes of nosocomial pneumonia, however, very little is known about the host immune response associated with pathogenesis of A. baumannii infection. Here, we used a hypervirulent A. baumannii to establish an acute lethal pneumonia, supported by high bacterial burdens, severe inflammatory cells infiltration and lung damage. The lung transcriptome changes in response to A. baumannii lethal pneumonia were detected by RNA sequencing. The results showed that 6288 host genes changed expression, with 3313 upregulated genes and 2975 downregulated genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that genes related to TNF, cytokine-cytokine receptor interaction, Toll-like receptor, NOD-like receptor, NF-κB, Jak-STAT, HIF-1 signaling pathways, apoptosis, and phagosome were significantly upregulated. Whereas genes associated with PI3K-AKT signaling pathway, glycolysis/gluconeogenesis, amino acid and fatty acid metabolism were downregulated. Immune cell typing highlighted the inflammatory response of innate immune cells headed by neutrophils. The reliability of RNA sequencing results were verified with selected differentially expressed genes by real-time PCR. This work provides an insight into the pathogenesis of lethal A. baumannii lung infection.